Optimization of Educational Play Methods to Enhance Children’s Concentration at TK Qur’ani Darul Muhsinin NW Gerantung, Embung Kandong Village - Romi Oriza; Ernawati (Journal of Education, Teaching, and Learning, 2025)
This study aims to examine the optimization of educational play methods in improving early childhood concentration at TK Qur’ani Darul Muhsinin NW Gerantung, Embung Kandong Village, during the 2024/2025 academic year. The core issues explored in this research include how teachers design and implement educational play strategies, the extent to which these strategies enhance children’s ability to concentrate, and the various supporting and inhibiting factors that influence their effectiveness in classroom practice. This study employs a descriptive qualitative approach to gain an in-depth understanding of the learning processes occurring in natural settings. Data were collected through in-depth interviews, participatory observation, and documentation. Informants consist of Group A and Group B teachers, the school principal, and selected parents, all chosen purposively based on their relevance to the research focus. The findings reveal that the use of educational play methods—such as puzzles, building blocks, movement-and-song games, storytelling, and role-playing—significantly enhances children’s concentration. These activities help young learners focus their attention, maintain concentration for longer periods, and reduce distractions that commonly occur during learning. Supporting factors include teachers’ creativity in selecting and modifying educational play tools, strong support from the school principal, and the availability of learning media that encourage active participation. On the other hand, inhibiting factors consist of limited learning time, insufficient variation of educational play tools, and differences in children’s developmental levels, particularly related to attention span. Overall, the study underscores the importance of integrating educational play strategies into early childhood learning to create an enjoyable, effective, and child-centered environment that supports optimal concentration development.